2020
DOI: 10.1136/annrheumdis-2020-218165
|View full text |Cite
|
Sign up to set email alerts
|

Experience of telemedicine use in a big cohort of patients with rheumatoid arthritis during COVID-19 pandemic

Abstract: We have read with interest the work of Bozzalla-Cassione et al 1 published recently in your journal regarding the implementation of a telemedicine programme for patients with lupus in northern Italy. It is logical to suppose that the risk of patients with rheumatic diseases of having a more severe clinical course if they become infected with the COVID-19 infection is very high; however, although some of the reports show that there seems to be a low incidence of COVID-19 infection in patients with rheumatic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Both cases underline the importance of shared decision making and emerging telemedicine systems in facilitating ongoing patient–physician communication and optimising healthcare during crises. 17 18 …”
Section: Discussionmentioning
confidence: 99%
“…Both cases underline the importance of shared decision making and emerging telemedicine systems in facilitating ongoing patient–physician communication and optimising healthcare during crises. 17 18 …”
Section: Discussionmentioning
confidence: 99%
“…Using tele-video meetings was limited to 1.7%. The risk of patients with rheumatic diseases of having a more severe clinical course if they become infected with the COVID-19 infection is very high and mandates the establishment of telemedicine programs [ 24 ]. The workflow of rheumatology outpatient clinics worldwide has changed.…”
Section: Discussionmentioning
confidence: 99%
“…McDougal et al ’s tele-rheumatology systematic review found that most studies reviewed ‘demonstrated a high risk of bias’ [ 11 ]; and studies have produced conflicting results. Some report high levels of patient satisfaction [ 12 , 13 ] and suggest that telemedicine could be as effective as face-to-face for autoimmune rheumatic diseases [ 14 ]. However, there are concerns regarding the use of telemedicine for diagnosis and assessment of disease activity [ 15 ], particularly as a result of lack of physical examinations [ 16 ].…”
Section: Introductionmentioning
confidence: 99%